Structural differences explain diverse functions of Plasmodium actins - Vahokoski, Juha; Bhargav, Saligram Prabhakar; Desfosses, Ambroise; Andreadaki, Maria; Kumpula, Esa-Pekka; Martinez, Silvia Muñico; Ignatev, Alexander; Lepper, Simone; Frischknecht, Friedrich; Sidén-Kiamos, Inga; Sachse, Carsten; Kursula, Inari (PLoS pathogens, 2014)
Actins are highly conserved proteins and key players in central processes in all eukaryotic cells. The two actins of the malaria parasite are among the most divergent eukaryotic actins and also differ from each other more than isoforms in any other species. Microfilaments have not been directly observed in Plasmodium and are presumed to be short and highly dynamic. We show that actin I cannot complement actin II in male gametogenesis, suggesting critical structural differences.
Gesehen am 25.09.2020